O efeito do treinamento de pilates solo em idosos institucionalizados frágeis e em risco de fragilização - Tatiana Lima Boletini (2022)
Frailty is a syndrome that involves declines in multiple domains, generating increased mortality and adverse events in the health of the elderly. Studies point to the importance of reducing sedentary lifestyle in institutionalized elderly, as changes in aging can be aggravated by new living conditions, making elderly people vulnerable to frailty. Thus, the Mat Pilates Method (MPS) presents itself as a powerful methodological proposal for the elderly population, although in the institutionalized elderly it is still little explored. The objective was to investigate the effect of MPS training on institutionalized elderly people at different levels of frailty, in physical, psychological and social aspects. The sample consisted of 26 frail elderly people at risk of frailty, all institutionalized, divided into two groups: Control Group (CG) and Intervention Group (IG). The elderly were submitted to frailty screening, using the Clinical-Functional Vulnerability Index – 20 (IVCF-20), and evaluated every 3 and 6 months using the Fried Frailty Phenotype and Edmonton Frailty Scale instruments to verify the level of frailty and its indicators according to physical, psychological and social aspects. Elderly people from IG participated in MPS classes, twice a week, lasting 1 hour/class for 6 months. After the intervention, the GI showed a decline in the level of frailty, indicating a significant improvement when compared to the CG, in relation to the physical aspects, the GI showed significant improvements through the indicators functional performance, increased grip strength and slow gait, while the CG showed a significant difference in weight loss; in the psychological aspects, the GI showed improvements in the cognition and mood indicators, while no significant differences were observed in the social aspects. The MPS had a strong influence on the decline in frailty of institutionalized elderly. It is concluded that the MPS had significant effects in relation to the level of frailty of the elderly in terms of physical and psychological aspects. Intervention with the pilates method altered the process of fragilization of the elderly in its various levels, attenuating the institutional vulnerability in which they found themselves at the beginning of the research.